Complex Concentrated Alloys (CCAs) Current Understanding and Future Opportunities - Mukherjee, Sundeep (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a collection of several unique articles on the current state of research on complex concentrated alloys, as well as their compelling future opportunities in wide ranging applications. Complex concentrated alloys consist of multiple principal elements and represent a new paradigm in structural alloy design. They show a range of exceptional properties that are unachievable in conventional alloys, including high strength-ductility combination, resistance to oxidation, corrosion/wear resistance, and excellent high-temperature properties. The research articles, reviews, and perspectives are intended to provide a wholistic view of this multidisciplinary subject of interest to scientists and engineers.